Can supervised exercise prevent treatment toxicity in patients with prostate cancer initiating androgen‐deprivation therapy: a randomised controlled trial. (27th July 2014) - Cormie, Prue; Galvão, Daniel A.; Spry, Nigel; Joseph, David; Chee, Raphael; Taaffe, Dennis R.; Chambers, Suzanne K.; Newton, Robert U.
<x xml:space="preserve">Abstract</x> Objective To determine if supervised exercise minimises treatment toxicity in patients with prostate cancer initiating androgen‐deprivation therapy (ADT). This is the first study to date that has investigated the potential role of exercise in preventing ADT toxicity rather than recovering from established toxicities. Patients and Methods Sixty‐three men scheduled to receive ADT were randomly assigned to a 3‐month supervised exercise programme involving aerobic and resistance exercise sessions commenced within 10 days of their first ADT injection (32 men) or usual care (31 men). The primary outcome was body composition (lean and fat mass). Other study outcomes included bone mineral density, physical function, blood biomarkers of chronic disease risk and bone turnover, general and prostate cancer‐specific quality of life, fatigue and psychological distress. Outcomes were compared between groups using analysis of covariance adjusted for baseline values. Results Compared to usual care, a 3‐month exercise programme preserved appendicular lean mass (P = 0.019) and prevented gains in whole body fat mass, trunk fat mass and percentage fat with group differences of −1.4 kg (P = 0.001), −0.9 kg (P = 0.008) and −1.3% (P < 0.001), respectively. Significant between‐group differences were also seen favouring the exercise group for cardiovascular fitness (peak oxygen consumption 1.1 mL/kg/min, P = 0.004), muscular strength (4.0–25.9 kg, P ≤ 0.026), lower body function (–1.1 s, P < 0.001), total cholesterol: high‐density lipoprotein‐cholesterol ratio (–0.52, P = 0.028), sexual function (15.2, P = 0.028), fatigue (3.1, P = 0.042), psychological distress (–2.2, P = 0.045), social functioning (3.8, P = 0.015) and mental health (3.6–3.8, P ≤ 0.022). There were no significant group differences for any other outcomes. Conclusion Commencing a supervised exercise programme involving aerobic and resistance exercise when initiating ADT significantly reduced treatment toxicity, while improving social functioning and mental health. Concurrent prescription of supervised exercise when initiating ADT is therefore advised to minimise morbidity associated with severe hypogonadism.